Investigating the existence of the environmental Kuznets curve in selected middle-income African countries - Dosini, Liyema (Rhodes University, 2026)
This study investigated the Environmental Kuznets Curve (EKC) hypothesis for five middle income African countries: Algeria, Angola, Morocco, Nigeria, and South Africa. The EKC hypothesis explores the relationship between economic growth and environmental degradation, suggesting an inverted U-shaped curve where environmental degradation rises during the early stages of growth but decreases once a certain income level is reached. This research employed annual panel and time series data from 1990 to 2019, excluding the post-2019 period, to avoid distortions caused by the COVID-19 pandemic. The study applied a range of econometric models, including Fixed Effects (FE), Random Effects (RE), Pooled Mean Group-Autoregressive Distributed Lag (PMG-ARDL), and timeseries Autoregressive Distributed Lag (ARDL) models. These models were used to estimate both short-run and long-run effects while accounting for heterogeneity across countries. In addition to GDP per capita and its square term to capture non-linearity, the analysis incorporated key structural control variables: trade openness, energy use and the human development index (HDI). The study aimed to contribute to the growing literature on the EKC within the African context. The panel models (PMG-ARDL) supported an inverted U-shaped EKC in most model specifications where the coefficients of GDP per capita and its squared term were statistically significant with the expected signs: a positive coefficient on GDP per capita and a negative coefficient on GDP per capita squared. The time-series ARDL findings revealed a U-shaped relationship between GDP per capita and CO₂ emissions for Algeria, Nigeria and South Africa, implying that continued economic growth is associated with increasing carbon emissions. For Angola, no evidence of the EKC was found as the GDP per capita squared coefficient was statistically insignificant in the best-fitting model, indicating a linear rather than quadratic relationship. The time-series ARDL results for Morocco provided weak and inconsistent evidence for the EKC hypothesis. These results highlight the need for context-specific environmental policies and suggest that economic growth alone may be insufficient to reduce emissions. The study contributes a deeper understanding of sustainable development challenges in African middle-income countries.
Keywords: Environmental economics (http://id.loc.gov/authorities/subjects/sh93004763); Environmental degradation (http://id.loc.gov/authorities/subjects/sh92006466); Economic development--Africa (http://id.loc.gov/authorities/subjects/sh85040804); Kuznets curve (https://www.wikidata.org/wiki/Q1349471); Politics of climate change (https://www.wikidata.org/wiki/Q1774427); Human Development Index (https://www.wikidata.org/wiki/Q38994); Energy mix (https://www.wikidata.org/wiki/Q1341346)